A Nurse-Run Public Health Clinic for Individuals Utilizing a Community Outreach Center. Issue 3 (3rd July 2021) - Doran, Kelly; Barrett, Barbara A; Buchanan, Marjorie
ABSTRACT: This article describes a nurse-run clinic for low-income individuals or individuals experiencing homelessness. We conducted a quality improvement project using data from 111 individuals over 194 visits. Thirty-seven percent of patients had difficulty managing their health and 22% reported being in an active health crisis. The visits resulted in patients leaving with their visit goal being met (86%), and 96% of nonemergent cases being diverted from the emergency room. The nurse-run clinic provided access to care and served as a safety net for a vulnerable population, providing support for this clinic model with this population.